2021
DOI: 10.3390/ijerph18094792
|View full text |Cite
|
Sign up to set email alerts
|

Protocol of a Single-Blind Two-Arm (Waitlist Control) Parallel-Group Randomised Controlled Pilot Feasibility Study for mHealth App among Incontinent Pregnant Women

Abstract: Background: The delivery of pelvic floor muscle training (PFMT) through mHealth apps has been shown to produce promising results in improving pelvic floor muscle strength and urinary incontinence (UI). However, there is limited evidence on mHealth apps designed for pregnant women who are at high risk of developing UI. This pilot study aims to evaluate the feasibility of conducting an effectiveness trial for a newly developed PFMT app among pregnant women in Malaysia. Methods: This is a prospective, single-cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…This protocol is designed according to referring guidelines, consensus and high-quality studies. As a multicenter RCT, it will involve ten hospitals including tertiary hospitals and maternity hospitals located in several provinces, purposed to achieve more convincing results than other single center protocols [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This protocol is designed according to referring guidelines, consensus and high-quality studies. As a multicenter RCT, it will involve ten hospitals including tertiary hospitals and maternity hospitals located in several provinces, purposed to achieve more convincing results than other single center protocols [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study was prospectively registered with ClinicalTrials.gov on 19 February 2021 (NCT04762433). The study protocol was designed and reported according to the Consolidated Standards of Reporting Trials (CONSORT) extension for randomised pilot and feasibility trials [ 20 , 21 ] and has been published recently [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…An online consent form was provided to eligible participants for their digital signature prior to the study commencement. The study protocol is designed and has been published elsewhere [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Subgroup assessments were analysed at baseline and two months after using the app. This study protocol was published recently [ 27 ] and prospectively registered with (NCT04762433).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the severity of UI and quality of life were also analysed. This paper reports the subgroup analysis of the pilot feasibility randomised controlled trial (RCT) study [ 27 ]. This feasibility and usability study will contribute preliminary evidence of the usability properties of a KEPT app designed with some of the persuasive features that were crucial to ensure engagement from the users [ 28 ].…”
Section: Introductionmentioning
confidence: 99%